21 Standardised implantable cardioverter defibrillator programming significantly reduces inappropriate and unnecessary therapy rates versus patient tailored programming. (June 2018) - Stodart, Clare; Wiles, Benedict; Banks, Phillip; Roberts, Paul; Yue, Arthur
Abstract : Background: Implantable cardioverter defibrillators (ICDs) can provide effective therapies for life-threatening ventricular arrhythmia (VA), whilst inappropriate and unnecessary therapies can cause physiological and psychological morbidity. The evidence base which underpins optimal ICD programming evolves rapidly. At our institution we introduced standardised programming for both primary (type 1) and secondary (type 2) prevention ICDs, utilising increased detection times and higher therapy zones in line with current best available evidence [figures 1 and 2]. In this study we retrospectively compared the inappropriate and unnecessary therapy rates of ICD patients who were switched from patient tailored to standardised programming during routine follow-up. Methods: A total of 200 patients, who had been routinely switched from patient tailored to standardised programming, were identified for analysis (mean age 72 years, 86% male, 75% primary prevention, 35% CRT, 64% coronary disease). Electronic records and physiologist follow-up reports were used to retrospectively analyse; episodes of VA, symptoms experienced, and therapies delivered. Therapies during the nine months prior to standardisation were compared statistically to the nine month period immediately following standardisation. Inappropriate therapies were defined as ATP or shock delivery in the absence of VA. For all episodes where symptom status could be established, unnecessary therapy rates were calculated as the percentage of ATP or shock therapies which were delivered during asymptomatic VA episodes. Results: There were a total of 1807 episodes of treated VA; 1300 occurring prior to standardisation (1230 ATP, 70 shocks) and 507 post (490 ATP, 17 shocks). Standardisation reduced the number of inappropriate ATP episodes from 59 to 1, and inappropriate shocks from 8 to 0. Standardisation reduced unnecessary ATP rates from 98.5% (n=1075) to 5.9% (n=456), whilst unnecessary shocks rates were reduced from 87.3% (n=55) to 41.2% (n=17). Conclusions: The application of standardised programming, using longer detection times and higher treatment zones, to patients undergoing ICD follow-up, significantly reduces the delivery of both inappropriate and unnecessary ATP and shocks.